Synthesis and characterization of novel heterocycles based on tetrazine and hydrazonoyl halides - Sayed, Abdelwahed Rashad; Al-Shihry, Shar Saad; Gomaa, Mohsen Abdel-Motaal (European Journal of Chemistry, 2014)
The present work describes the preparation and characterization of new pyridazine, thiohydrazonate, bis-pyrazole, bis-triazole and polypyrazoles based on tetrazine and hydrazonoyl halides. The structures of the newly synthesized were elucidated on the basis of their spectral data FT-IR, NMR, Mass and elemental analysis.